jurnal Jurnal syekh 2024.pdf: unka jurnal - Mochsin, Syekh (Universitas Kapuas Sintang, 2025)
Abstract: The problem raised in this research is the Quality of Public Services at the Sokan Sub-district Office, Melawi Regency. Based on the Research Results that the Quality of Service is based on the Decree of the Regent of Melawi Regency, concerning the Determination of Sub-districts in Melawi Regency as the organizer of Sub-district Administration services, this Decree of the Regent of Melawi is about the initial stages of implementing service policies related to standard operating procedures in Sub-districts in Melawi Regency. Service time With the existence of service standards published to the public, it will provide information to the public regarding the timeliness of completing their administrative files.. However, in addition to these standards, transparency from service officers regarding service completion times is also required. Service procedures remain guided by the Sokan District Administrative Service Guidelines, which are first guided by Minister of Home Affairs Regulation Number 4 of 2010 concerning